2014
DOI: 10.1103/physrevc.89.011302
|View full text |Cite
|
Sign up to set email alerts
|

Toward a unified realistic shell-model Hamiltonian with the monopole-based universal force

Abstract: We propose a unified realistic shell-model Hamiltonian employing the pairing plus multipole Hamiltonian combined with the monopole interaction constructed starting from the monopole-based universal force by Otsuka et al. (Phys. Rev. Lett. 104, 012501 (2010)). It is demonstrated that the proposed PMMU model can consistently describe a large amount of spectroscopic data as well as binding energies in the p f and p f 5/2 g 9/2 shell spaces, and could serve as a practical shell model for even heavier mass regions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
(61 reference statements)
1
22
0
2
Order By: Relevance
“…Here the sign ≈ is related to the expected anharmonicities coming from the "blocking" of the odd neutron. Shell-model calculations performed using the V low-k approach [34] or a unified realistic Hamilto-nian with a monopole based universal force [35] show that almost 90% of the strength is exhausted by the 5/2 + , 13/2 + , and 11/2 + members of the multiplet, with the 13/2 + state giving the dominant contribution (see below for shell-model calculations).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the sign ≈ is related to the expected anharmonicities coming from the "blocking" of the odd neutron. Shell-model calculations performed using the V low-k approach [34] or a unified realistic Hamilto-nian with a monopole based universal force [35] show that almost 90% of the strength is exhausted by the 5/2 + , 13/2 + , and 11/2 + members of the multiplet, with the 13/2 + state giving the dominant contribution (see below for shell-model calculations).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Shell-model calculations have been performed using SM1, a unified realistic interaction employing the pairing plus multipole Hamiltonian combined with the monopole interaction constructed starting from the monopole-based universal force from Refs. [35,36], or SM2, an effective Hamiltonian derived from the CD-Bonn potential, renormalized by way of the V low-k approach [37], within the framework of the timedependent perturbation theory [34].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deneysel sonuçlar [1] incelendiğinde, bu farklılıklar kararlılık eğrisinde bölgelere göre ve izotop, izoton, izobar çizgileri boyunca gözlenebilmektedir. Son yıllarda, A~50 bölgesinde yer alan orta kütleli çift-çift Fe izotopları için ile yapılan deneysel çalışmaların yanında, kabuk modeli, QRPN, etkileşen bozon modeli (IBM) gibi bazı modeller ile çalışmalar gerçekleştirilmiştir [2][3][4][5][6][7][8][9]. Çift-çift 50,52,54,56,58,60 Fe izotoplarının kuantum şekil faz geçişleri teorik olarak incelenmiştir [2].…”
Section: Introductionunclassified
“…[47] predicted a delay in the band crossing frequency in the N ¼ Z nuclei 84 42 Mo 42 and 88 44 Ru 44 as an effect of enhanced neutron-proton interactions. Kaneko et al [48] employed LSSM calculations using a "pairing-plus-multipole" Hamiltonian [49] in the ð1p 1=2 ; p 3=2 ; f 5=2 ; g 9=2 ; d 5=2 Þ (often denoted as fpgd) model space for studying 88 44 Ru 44 , 90 44 Ru 46 , and 92 44 Ru 48 and concluded that T ¼ 0 np pairing is responsible for the distinct difference in rotational behavior between the N ¼ Z and N > Z nuclei. These calculations also predicted a significant delay in the band crossing frequency for N ¼ Z and their prediction for the J ð1Þ moment of inertia of 88 44 Ru 44 revealed a sharp irregularity at a rotational frequency ℏω c ≈ 0.65 MeV [48].…”
mentioning
confidence: 99%